Nutrition in pregnancy. Issue 9 (September 2016) - Ho, Alison; Flynn, Angela C.; Pasupathy, Dharmintra
Abstract: The pivotal role of nutrition in pregnancy is well established and has important implications on subsequent maternal and offspring health, including outcomes in later adult life. Optimal nutrition periconception, if maintained throughout pregnancy, promotes optimal foetal growth and development. Growth trajectories in utero and size at birth are related to the offspring's risk of developing disease in later life, especially chronic non-communicable diseases such as hypertension, diabetes and coronary heart disease (the Barker hypothesis). This article aims to review nutritional requirements in pregnancy, describe their transport mechanisms and highlight the implications of inadequate or inappropriate intake. Nutritional requirements are broadly divided into issues surrounding quality (macronutrients and micronutrients) and quantity of intake with a final summary of current International Federation of Gynaecology and Obstetrics (FIGO) and Royal College of Obstetricians and Gynaecologists (RCOG) recommendations.